Effect of high-frequency modes on singlet fission dynamics - Fujihashi, Yuta (2017)
Singlet fission is a spin-allowed energy conversion process whereby a singlet excitation splits into two spin-correlated triplet excitations residing on adjacent molecules and has a potential to dramatically increase the efficiency of organic photovoltaics. Recent time-resolved nonlinear spectra of pentacene derivatives have shown the importance of high frequency vibrational modes in efficient fission. In this work, we explore impacts of vibration-induced fluctuations on fission dynamics through quantum dynamics calculations with parameters from fitting measured linear and nonlinear spectra. We demonstrate that fission dynamics strongly depends on the frequency of the intramolecular vibrational mode. Furthermore, we examine the effect of two vibrational modes on fission dynamics. Inclusion of a second vibrational mode creates an additional fission channel even when its Huang-Rhys factor is relatively small. Addition of more vibrational modes may not enhance the fission per se, but can dramatically affect the interplay between fission dynamics and the dominant vibrational mode.